Local TV stations in peru. A history of use as political tools: the juliaca case - Dettleff, James A. (Folios, revista de la Facultad de Comunicaciones y Filología, 2012)
This article is about the history of local TV stations in the Andean cityof Juliaca, in Puno, Peru. As we learn the history of these stations, we can see the way local voices face the centralized production system in Peru, the limited resources they have to produce their shows, and the way these stations -mainly their news programs- become tools to make the owners or anchors gain access to public offices as majors or congress members. The author has visited the city for these research three times in a five year span, allowing him watch the changes in the TV stations, interview most of its owners, and make a survey to over 300 viewers of the city.